KUFRI KARAN-FIRST MULTIPLE DISEASE RESISTANT, HIGH YIELDING POTATO VARIETY FOR CULTIVATION IN HILLS AND PLATEAUX OF INDIA - Sood, Salej (Potato Journal, 2021)
Kufri Karan is a ‘First’ potato variety developed by indigenous potato breeding program possessingresistance to multiple diseases, medium maturing and high yielding suitable for cultivation in hills and plateaux of thecountry. During the developmental stages, marker assisted selections were effected to ascertain the phenotypic resistancesat genetic level to ensure the stacking of functional, multiple genes imparting resistance to different biotic stresses. Thevariety possesses high resistance to late blight, six viruses i.e. ToLCNDV-potato, PVY, PLRV, PVA, PVM and PVS andmoderate resistance to Potato Cyst Nematode. The variety produces attractive, white cream, ovoid tubers with shalloweyes and creamy flesh, medium dormancy and good keeping quality. The tubers are easy to cook, has acceptable aromapost cooking with mealy texture. It yields higher than varieties Kufri Jyoti, Kufri Himalini and Kufri Girdhari, with anaverage yield of the variety is 25-30 t/ha under normal conditions of crop growth in the hills and plateaux, while in subtropicalplains the tuber yield is >30 t/ha. This variety being resistant to multiple biotic stresses will be an economicalalternative to earlier varieties being cultivated in the areas where late blight, viruses and PCN are major impedimentsto potato cultivation.